Relationship Between School Head Supervision and Organizational Climate with Teacher Performance in Almadrasah Aliyah, Kualuh Leidong District - Hikmatul Hidayah; Hera Herviana (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
Madrasah quality is one of the most urgent in the world of education. in this study will attempt to reveal the relationship between madrasah head leadership and teacher work participation with madrasah quality. The research method uses correlational research, namely research that seeks to see the relationship between variables. The study population was all MTs teachers in Labuhan Batu District totaling 83 people. The sample was taken using proportional random sampling technique, so that the sample was taken as many as 75 people. The instrument used was a questionnaire, data analysis techniques were carried out with data descriptions, and hypothesis testing using simple regression and multiple regression. The following results were obtained: 1) There was a positive and significant relationship between the leadership of the madrasah head (X1) and the madrasah quality (Y) in the Madrasah Tsanawiyah Labuhan Batu with moderate correlation levels with the correlation coefficient value of 0.092. While the value of the strength of the relationship that occurs between the two variables is 0.092 or 8%. 2) There is a positive and significant relationship between teacher work participation (X2) and the quality of madrasah (Y) in Laban Batu Tsanawiyah Madrasah with a moderate level of correlation with the correlation coefficient value of 0.390. While the value of the strength of the relationship that occurs between the two variables is 0.390 or 15.2%. 3) There is a positive and significant relationship between madrasah head leadership (X1) and teacher work participation (X2) with madrasah quality (Y) in Laban Batu Tsanawiyah Madrasah with moderate correlation levels with a correlation coefficient value of 0.512. While the value of the strength of the relationship that occurs between the two variables is 0.512 or 26.2%.